Features of the State of Cellular and Humoral Markers of the Immune System in Breast Cancer among Women in Aktobe Region - Zhexenova, Azhar; Kaldybaeva, Aiman; Amanzholkyzy, Ainur; Taskozhina, Gulaim; Kurmangalieva, Saulesh; Almagambetova, Altyn; Gubasheva, Gulnara; Mukyshova, Gulbanu; Yegisbaeva, Dina (Open Access Macedonian Journal of Medical Sciences, 2022)
Abstract BACKGROUND: Globally, breast cancer is considered one of the most common cancers among women and the second most common cancer worldwide. Breast cancer is also more common in developed countries, and its prevalence is increasing globally by 2% each year. AIM: The aim of this study is to determine the features of the state of cellular and humoral markers of the immune system, as well as the relationship of specific and nonspecific immunity in women in the compared groups in breast cancer in Aktobe region. METHODS: The study was conducted on 251 patients at Medical Center of West Kazakhstan Marat Ospanov Medical University with the established diagnosis of breast cancer. The study period was 3 years (2018-2020). Acknowledgements. Authors declare the absence of conflict of interest. The study is funded by the Ministry of Education and Science of the Republic of Kazakhstan project IRN 0118RK01065. Two groups of patients were formed, among them in the control group - BC before chemotherapy and in the main group - BC after chemotherapy. To address the objectives, in addition to the general clinical study, all patients were conducted immune system study. CD3+CD19-, CD3-CD19+, CD4+CD8-,CD4-CD8+, IRI, CD3+HLA-DR+, NK(CD16+56+), CD3+/CD16+56+ ; and to determine humoral immunity, the content of JgM, JgG, JgA were determined. RESULTS: Correlation analysis revealed a strong positive relationship between IRI and T helper (CD4+CD8-) (r=0.79; p≤0.05) and a strong negative correlation between T cytotoxic lymphocyte (CD4-CD8+) and IRI (r= -0.8; p≤0.05) in both patient groups. The ratio of the two T cell subpopulations CD4+/T cell CD8+ is at the regulatory T cell level (IRI). A direct median correlation between T lymphocyte (CD3+CD19-) and T killer (CD3+/CD16+56+) r= 0.35; (p≤0.05) was found, which indicates an integral regulatory role of natural killer cells in immune system function. The following coorelation analysis showed a weak negative association between cellular and humoral immunity in the control group of women between T cytotoxic lymphocytes (CD4-CD8+) and IgG(r=-0.2; p≤0.05). Further, the relationship revealed between cellular and humoral immunity in the main group between IG M and NK cells (r= -0.2; p≤0.05). CONCLUSION: It can be assumed that identifying the possibility of altering the antitumor immune response before and after chemotherapy in patients with a primary breast tumor may set the stage for its early detection and application of targeted chemoprophylaxis. Abstract BACKGROUND: Globally, breast cancer is considered one of the most common cancers among women and the second most common cancer worldwide. Breast cancer is also more common in developed countries, and its prevalence is increasing globally by 2% each year. AIM: The aim of this study is to determine the features of the state of cellular and humoral markers of the immune system, as well as the relationship of specific and nonspecific immunity in women in the compared groups in breast cancer in Aktobe region. METHODS: The study was conducted on 251 patients at Medical Center of West Kazakhstan Marat Ospanov Medical University with the established diagnosis of breast cancer. The study period was 3 years (2018-2020). Acknowledgements. Authors declare the absence of conflict of interest. The study is funded by the Ministry of Education and Science of the Republic of Kazakhstan project IRN 0118RK01065. Two groups of patients were formed, among them in the control group - BC before chemotherapy and in the main group - BC after chemotherapy. To address the objectives, in addition to the general clinical study, all patients were conducted immune system study. CD3+CD19-, CD3-CD19+, CD4+CD8-,CD4-CD8+, IRI, CD3+HLA-DR+, NK(CD16+56+), CD3+/CD16+56+ ; and to determine humoral immunity, the content of JgM, JgG, JgA were determined. RESULTS: Correlation analysis revealed a strong positive relationship between IRI and T helper (CD4+CD8-) (r=0.79; p≤0.05) and a strong negative correlation between T cytotoxic lymphocyte (CD4-CD8+) and IRI (r= -0.8; p≤0.05) in both patient groups. The ratio of the two T cell subpopulations CD4+/T cell CD8+ is at the regulatory T cell level (IRI). A direct median correlation between T lymphocyte (CD3+CD19-) and T killer (CD3+/CD16+56+) r= 0.35; (p≤0.05) was found, which indicates an integral regulatory role of natural killer cells in immune system function. The following coorelation analysis showed a weak negative association between cellular and humoral immunity in the control group of women between T cytotoxic lymphocytes (CD4-CD8+) and IgG(r=-0.2; p≤0.05). Further, the relationship revealed between cellular and humoral immunity in the main group between IG M and NK cells (r= -0.2; p≤0.05). CONCLUSION: It can be assumed that identifying the possibility of altering the antitumor immune response before and after chemotherapy in patients with a primary breast tumor may set the stage for its early detection and application of targeted chemoprophylaxis. Abstract BACKGROUND: Globally, breast cancer is considered one of the most common cancers among women and the second most common cancer worldwide. Breast cancer is also more common in developed countries, and its prevalence is increasing globally by 2% each year. AIM: The aim of this study is to determine the features of the state of cellular and humoral markers of the immune system, as well as the relationship of specific and nonspecific immunity in women in the compared groups in breast cancer in Aktobe region. METHODS: The study was conducted on 251 patients at Medical Center of West Kazakhstan Marat Ospanov Medical University with the established diagnosis of breast cancer. The study period was 3 years (2018-2020). Acknowledgements. Authors declare the absence of conflict of interest. The study is funded by the Ministry of Education and Science of the Republic of Kazakhstan project IRN 0118RK01065. Two groups of patients were formed, among them in the control group - BC before chemotherapy and in the main group - BC after chemotherapy. To address the objectives, in addition to the general clinical study, all patients were conducted immune system study. CD3+CD19-, CD3-CD19+, CD4+CD8-,CD4-CD8+, IRI, CD3+HLA-DR+, NK(CD16+56+), CD3+/CD16+56+ ; and to determine humoral immunity, the content of JgM, JgG, JgA were determined. RESULTS: Correlation analysis revealed a strong positive relationship between IRI and T helper (CD4+CD8-) (r=0.79; p≤0.05) and a strong negative correlation between T cytotoxic lymphocyte (CD4-CD8+) and IRI (r= -0.8; p≤0.05) in both patient groups. The ratio of the two T cell subpopulations CD4+/T cell CD8+ is at the regulatory T cell level (IRI). A direct median correlation between T lymphocyte (CD3+CD19-) and T killer (CD3+/CD16+56+) r= 0.35; (p≤0.05) was found, which indicates an integral regulatory role of natural killer cells in immune system function. The following coorelation analysis showed a weak negative association between cellular and humoral immunity in the control group of women between T cytotoxic lymphocytes (CD4-CD8+) and IgG(r=-0.2; p≤0.05). Further, the relationship revealed between cellular and humoral immunity in the main group between IG M and NK cells (r= -0.2; p≤0.05). CONCLUSION: It can be assumed that identifying the possibility of altering the antitumor immune response before and after chemotherapy in patients with a primary breast tumor may set the stage for its early detection and application of targeted chemoprophylaxis.